AN INTEGRATED ANIMAL HUSBANDRY LIVESTOCK MANAGEMENT SYSTEM - Saravanan, K.; Saranya, S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Agriculture is the main source of income in countryside areas. Animal such as cow, buffalo, sheep, goat play an important role in life of rural and source of income. A Lot of farmers are now tormenting from different diseases and increase breeding cost. In modern era, compact and simple device has made animal monitoring increasingly attractive. However animal heat detection is still a complicated and inconvenient method. A complete integrated information and Communication Technology is described to design and characterize wearable collar monitoring device for Animal monitoring system and also identify the animal health, heat stress and fertility for Artificial insemination during the livestock Monitoring. A wearable collar based device with sensors wear to a neck of the animal is designed in helping user to better manage the animalâ€™s dynamic information retrieving and analysing over a wireless network. Farmer can monitor animal condition at distance via wireless communication and take timely actions in case of emergency.Â  Cloud based frame work has been proposed for livestock Animal Husbandry which with be beneficial IoT healthcare solution.